Photocatalytic esterification under Mitsunobu reaction conditions mediated by flavin and visible light - März, M; Chudoba, J; Kohout, M; Cibulka, R (Organic & biomolecular chemistry, 2017)
The usefulness of flavin-based aerial photooxidation in esterification under Mitsunobu reaction conditions was demonstrated, providing aerial dialkyl azodicarboxylate recycling/generation from the corresponding dialkyl hydrazine dicarboxylate. Simultaneously, activation of triphenylphosphine (Ph3P) by photoinduced electron transfer from flavin allows azo-reagent-free esterification. An optimized system with 3-methylriboflavin tetraacetate (10%), oxygen (terminal oxidant), visible light (450 nm), Ph3P, and dialkyl hydrazine dicarboxylate (10%) has been shown to provide efficient and stereoselective coupling of various alcohols and acids to esters with retention of configuration.